Sequential quality competition in the restaurant industry: effects of restaurants’ reputation - Ferreira, Fernanda A. (2022)
In the present paper, a model has been considered, in which two asymmetric restaurants, with respect to their reputations, compete, non-cooperatively, on both quality and quantities. First, at the quality stage, restaurants take their decisions sequentially, with the small restaurant acting as a leader. Then, at the quantity stage, both restaurants take their decisions simultaneously. The aim is twofold: the first is to compute the decisions that give higher profits and the second is to study the effects of the difference of restaurants’ reputation. One of the main results of the research is that the reputation is an important feature, influencing the comparative results of the two restaurants in qualitative terms. In fact, reputation difference decreases the profits of the small (leader) restaurant, while it can either increase or decrease the profits of the large (follower) restaurant. However, less reputation difference between the restaurants decreases social welfare.